Prepectoral and Subpectoral Tissue Expander–Based Breast Reconstruction: A Propensity-Matched Analysis of 90-Day Clinical and Health-Related Quality-of-Life Outcomes. Issue 4 (31st January 2022) - Nelson, Jonas A.; Shamsunder, Meghana G.; Vorstenbosch, Joshua; Polanco, Thais O.; Matros, Evan; Coriddi, Michelle R.; Mehrara, Babak J.; Allen, Robert J.; Dayan, Joseph H.; Disa, Joseph J.
Abstract : Background: Prepectoral placement of tissue expanders for two-stage implant-based breast reconstruction potentially minimizes chest wall morbidity and postoperative pain. The authors explored 90-day clinical and health-related quality-of-life outcomes for prepectoral versus subpectoral tissue expander breast reconstruction. Methods: The authors conducted a propensity score-matching analysis (nearest neighbor, 1:1 matching without replacement) of patients who underwent immediate prepectoral or subpectoral tissue expander breast reconstruction between December of 2017 and January of 2019. Matched covariates included age, body mass index, race/ethnicity, smoking status, chemotherapy, radiotherapy, nipple-sparing mastectomy, and laterality of reconstruction. Outcomes of interest were perioperative analgesia use, 90-day postoperative patient-reported pain, complication rates, and BREAST-Q physical well-being of the chest scores. Results: Of the initial cohort of 921 patients, 238 were propensity-matched and included in the final analysis. The matched cohort had no differences in baseline characteristics. Postoperative ketorolac ( p = 0.048) use was higher in the subpectoral group; there were no other significant differences in intraoperative and postoperative analgesia use. Prepectoral patients had lower pain on postoperative days 1 to 2 but no differences on days 3 to 10. BREAST-Q physical well-being of the chest scores did not differ. Prepectoral patients had higher rates of seroma than subpectoral patients ( p < 0.001). Rates of tissue expander loss did not differ. Conclusions: This matched analysis of 90-day complications found lower early postoperative pain in prepectoral tissue expander patients but no longer-term patient-reported differences. Although prepectoral reconstruction patients experienced a higher rate of seroma, this did not translate to a difference in tissue expander loss. Long-term analysis of clinical and patient-reported outcomes is needed to understand the full profile of the prepectoral technique. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.